Kinerja Aspal Pertamina Pen 60/70 Dan Aspal Bna Blend 75/25 Pada Campuran Aspal Panas AC-WC - Leily Fatmawati (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2013)
The road is the basic infrastructure and major in propelling the national economy and local governments, considering important and its strategic function of road to push the distribution of goods and services as well as the population mobility. It is necessary for planning the structure of his stardom is a strong, durable and have a high durability against plastis deformation. As a indication factor if the cause of the overload or often called Physical Damage factor (P.D.F.), load repetition and drainage function less well. The third factor is the main cause of damage to road roughness is demanding the use of the material for the road roughness with better quality, in the form of aggregate materials as fillers are primarily asphalt or as a binder. This research was conducted to measure up to abaout performance of the asphalt Pertamina Pen 60/70 and BNA Blend 75/25 on hot mix asphalt AC-WC to the characteristics of the Marshall and the results are expected to provide information in the field of street work. The results showed that the value of the characteristics of Marshall on the optimum asphalt content (OBC), the mixture of the Laston AC-WC using BNA Blend 75/25 (mixture “B”) has better characteristics than the Laston AC-WC using asphalt Pertamina Pen 60/70 (mixture “A”). Shown with Marshall Stability on mixture “B”amounted to 1088.621 kg higher than the mixture “A” amounted to 891.902 kg. Marshall Quotient (MQ) value mixture “B” amounted to 327.86 kg/mm higher than the mixture “A” amounted to 284.98 kg/mm, can be interpreted as indicating a high ability of MQ receive traffic load repetition, friction wheels of vehicels on the road surface and the ability to withstand wear and tear due to the influence of temperature changes. From these results reinforce answered the initial hypothesis that the BNA Blend 75/25 is more durable than asphalt Pertamina Pen 60/70.